The Analysis of the Power in Donald Trump’s Speech - Kadariyah, Nur Laila; Hana Sazida (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2024)
Effectively, a speech's contents and the choice of words can reflect and describe the speakers’ personalities or characters and their power. It can shape the public’s perception, be influenced by the figure, and reflect the speakers' viewpoints. This research used Norman Fairclough’s Critical Discourse Analysis (CDA) to identify the power in Donald Trump’s speech which was delivered on National Security and Terrorism in The Wake of The Orlando Massacre on June 13, 2016, at Saint Anselm College in Manchester.  The text analysis proved that the power was represented through Pronouns, Repetition, Diction, Synonyms, Antonyms, and Assumptions. Discursive Practice showed the power came from the terrorism incident could bring into a sensitive issue that got many responses and attention from the public. The power also came from his social status in the community and institutions, both in politics and business. Trump’s rank socially made him get a lot of support.